A Bioinspired Material for Bone Tissue Regeneration: The Use of Ganoderma sessile Mycelium as a Microstructure Director - Noelia Laura D’Elía; Javier Sartuqui; Damian Placente; Pablo Postemsky; Paula Verónica Messina (Proceedings)
Introduction [...]